The role of green roofs on reducing heating and cooling loads: a database across Chinese climates - Kokogiannakis, Georgios; Tietje, Annegret; Darkwa, Jo (Elsevier, 2011)
This paper aims to use detailed modelling techniques and develop a database for assessing in a quick and easy way the energy performance of green roof designs across a range of Chinese climates. The focus is on heating and cooling loads by calculating indoor temperatures using the EnergyPlus simulation tool. The study covers 5328 configurations by varying model parameters such as location, climate, seasonal periods, glazing type, wall insulation levels, roof insulation, soil thickness and condition, and vegetation density characteristics. It was found from the results that green roofs can offer significant energy savings for heating and cooling loads if they are applied on roofs without insulation but only limited energy savings where heavy insulation on the roof is also applied. This database can prove to be a useful tool to the practitioners who want to perform rapid assessments of the potential energy savings that could be gained from a green roof installation in a Chinese location.